Clinical Frailty Scale for Risk Stratification in Patients with Sars-Cov-2 Infection. (August 2020) - Labenz, Christian; Kremer, Wolfgang M.; Schattenberg, Jörn M.; Wörns, Marcus-Alexander; Toenges, Gerrit; Weinmann, Arndt; Galle, Peter R.; Sprinzl, Martin F.
Predictive factors for adverse outcomes in patients with COVID-19 are urgently needed. Data related to the applicability of the Clinical Frailty Scale (CFS) for risk stratification in patients with COVID-19 are currently lacking. We investigated the ability of CFS to predict need for mechanical ventilation and the duration of hospital stays in European patients with COVID-19. In total, 42 patients with confirmed COVID-19 infection admitted to the University Medical Center Mainz between March 3 and April 15 2020 were included into this validation study and data were retrospectively analyzed. CFS was assessed at admission in all patients. Patients were followed for need for mechanical ventilation and time to hospital discharge. At admission, the median CFS was 3 (range: 1-7) and 14 (33.3%) patients were considered as at least pre-frail (CFS >3). 24 (57.1%) patients were discharged from hospital after a median time of 7 days (IQR 4-8). 12 (28.6%) patients developed acute respiratory distress syndrome and required mechanical ventilation. In multivariable Cox regression analyses, higher CFS scores (HR 1.659, 95% CI 1.090 to 2.525, p=0.018) were an independent predictor for a higher risk of mechanical ventilation after adjusting for age, Charlson Comorbidity Index and quick sepsis-related organ failure score. Additionally, lower CFS scores (HR 0.554, 95% CI 0.312 to 0.983, p=0.043) were associated with earlier discharge from hospital. In conclusion, this report demonstrates the usefulness of the CFS for risk stratification at hospital admission in patients with COVID-19.